2012
DOI: 10.4103/0971-6580.97223
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid and thiamethoxam induced mutations in internal transcribed spacer 2 (ITS2) of Anopheles stephensi

Abstract: The present article deals with the polymerase chain reaction (PCR)-based genotoxicity evaluation of neonicotinoid pesticides, imidacloprid and thiamethoxam, by using the genome of a mosquito Anopheles stephensi taken as an experimental model. After treatment of the second instar larvae with LC20 of the pesticides for 24 h, the induced nucleotide sequence variations in the internal transcribed spacer 2 (ITS2) of freshly hatched unfed control and treated individuals was studied from the sequence alignment data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…More recently, some hematobiochemical studies confirmed that anemia and alterations of liver and kidney biomarkers were reliable findings in TMX treated cockerels [ 8 ], birds [ [9] , [10] , [11] ], fish [ 12 , 13 ], and rats [ [14] , [15] , [16] ]. Besides, the mutagenic effect of TMX has been demonstrated in many studies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some hematobiochemical studies confirmed that anemia and alterations of liver and kidney biomarkers were reliable findings in TMX treated cockerels [ 8 ], birds [ [9] , [10] , [11] ], fish [ 12 , 13 ], and rats [ [14] , [15] , [16] ]. Besides, the mutagenic effect of TMX has been demonstrated in many studies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…stephensi , numerous ITS2 sequences are available in the GenBank and research publications [ 2 , 8 , 10 , 26 – 28 ]. However, polymorphism in length and nucleotide sequence has been observed in sequences reported from Iran [ 26 ], India [ 28 ], and in several GenBank sequences. Such intraspecific polymorphism is intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…In another study the LC 50 against yellow fever mosquito was 0.03 mg/l for imidacloprid, 0.06 mg/l for acetamiprid and 0.007 mg/l for thiamethoxam and 0.11 mg/l for dinotefuran 15 . Bhinder et al 16 compared the toxicity of imidacloprid and thiamethoxam in An. stephensi Liston (Diptera: Culicidae) and noticed measurable differences in internal transcribed spacer 2 (ITS2) sequences of control and treated mosquitoes indicating genetic damage.…”
mentioning
confidence: 99%